Baseline AHR expression shapes immune response to pharmacological modulation in PBMCs from pancreatic cancer patients - Bartkeviciene, Arenida; Jasukaitiene, Aldona; Zievyte, Inga; Ivanauskiene, Sandra; Stachneviciute, Gabija; Jenceviciute, Kornelija; Karvelyte, Gabriele; Stukas, Darius; Sikarske, Agne; Urboniene, Daiva; Maimets, Toivo; Jaudzems, Kristaps; et al. (Frontiers in Immunology, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) remains largely unresponsive to immunotherapy because of its highly immunosuppressive tumor microenvironment. Aryl hydrocarbon receptor (AHR), a ligand-dependent transcription factor, has emerged as a key regulator of immune homeostasis and inflammation. However, its systemic immunomodulatory role in PDAC, particularly outside the tumor microenvironment, remains poorly understood.MethodsPeripheral blood mononuclear cells (PBMCs) from patients with PDAC and healthy donors were isolated and treated ex vivo with two AHR agonists (Carbidopa and Tapinarof) and one antagonist (BAY 2416964). The samples were stratified into Low and High/Medium AHR expression groups. Flow cytometry (FC), qPCR, ELISA, Luminex assays, and immunofluorescence imaging were used to evaluate immune checkpoint expression, cytokine secretion, monocyte polarization, and subcellular AHR localization. Overall survival analysis was performed based on the baseline AHR expression levels.ResultsBaseline AHR expression strongly influenced the immunological effects of AHR modulators. In High/Medium AHR PBMCs, Carbidopa increased PD-L1 and soluble PD-1 (sPD-1) levels, while IL10 expression was suppressed. In contrast, BAY significantly reduced PD-1 and sPD-1 levels in Low AHR PBMCs, whereas Tapinarof induced the highest IL10 expression. All modulators reduced the proportion of M2-like monocytes, indicating a shift toward less immunosuppressive phenotypes. Nuclear translocation of AHR protein varied across treatments and expression levels. Kaplan–Meier analysis revealed a non-significant trend toward improved overall survival in the High/Medium AHR group (log-rank p = 0.276).ConclusionBaseline AHR expression critically shapes the immune response to pharmacological modulation in PBMCs from PDAC patients. These findings suggest that AHR profiling may serve as a clinically relevant biomarker for stratifying patients and guiding personalized immunotherapy approaches for PDAC.